1999
DOI: 10.1056/nejm199901283400403
|View full text |Cite
|
Sign up to set email alerts
|

Twice-Daily Compared with Once-Daily Thoracic Radiotherapy in Limited Small-Cell Lung Cancer Treated Concurrently with Cisplatin and Etoposide

Abstract: Four cycles of cisplatin plus etoposide and a course of radiotherapy (45 Gy, given either once or twice daily) beginning with cycle 1 of the chemotherapy resulted in overall two- and five-year survival rates of 44 percent and 23 percent, a considerable improvement in survival rates over previous results in patients with limited small-cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

38
798
13
26

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,335 publications
(883 citation statements)
references
References 23 publications
38
798
13
26
Order By: Relevance
“…This may have been due to the higher total RT doses used in the head and neck (60 -70 Gy), although we could not establish clearly a dose-response relation, the higher response to induction therapy, or both. Although there is evidence that concurrent chemoradiation rather than sequential chemoradiation is a more effective method for inducing a complete clinical response in patients with small cell lung carcinoma, [25][26][27] sequential chemoradiation appears to be an adequate and less toxic means of securing local control for most patients with NSNEC.…”
Section: Discussionmentioning
confidence: 99%
“…This may have been due to the higher total RT doses used in the head and neck (60 -70 Gy), although we could not establish clearly a dose-response relation, the higher response to induction therapy, or both. Although there is evidence that concurrent chemoradiation rather than sequential chemoradiation is a more effective method for inducing a complete clinical response in patients with small cell lung carcinoma, [25][26][27] sequential chemoradiation appears to be an adequate and less toxic means of securing local control for most patients with NSNEC.…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive radiotherapy or concurrent chemo-radiation therapy for lung cancer is standard care for patients with locally advanced disease, i.e. stage III non-small cell lung cancer (NSCLC) or limited stage small cell lung carcinoma (LD-SCLC) [3,4].Combined concurrent modality treatment increases long-term survival, but at the expense of a higher incidence of severe esophagitis [5][6][7][8]. In order to allow proper balancing between expected benefits and drawbacks of aggressive therapy, knowledge of the effects of a given treatment on the quality of life (QoL) is needed.…”
mentioning
confidence: 99%
“…1,[15][16][17][18][19] To administer this three-drug combination safely, doses of all three drugs were reduced compared with the doses feasible in various two-drug combinations. Even with the routine use of granulocyte-colony stimulating factor (G-CSF), our previous Phase I trial demonstrated that dose-limiting thrombocytopenia prevented meaningful dose escalation.…”
Section: Discussionmentioning
confidence: 99%
“…Improved methods of combining chemotherapy and radiation therapy have resulted in survival improvements for patients with limited stage small cell lung carcinoma: recent large trials have documented a median survival of 20 -24 months, with 20% of patients disease free at 4 -5 years. 1 During the last several years, the introduction of several active new agents has led to improvements in therapy for patients with a number of epithelial malignancies. Several of these new drugs, including the taxanes, topotecan, irinotecan, and gemcitabine, are active in the first-line treatment of patients with extensive stage small cell lung carcinoma, with response rates ranging from 20% to 50%.…”
mentioning
confidence: 99%